2023
DOI: 10.1002/smll.202301673
|View full text |Cite
|
Sign up to set email alerts
|

Real‐Time, In Situ Imaging of Macrophages via Phase‐Change Peptide Nanoemulsions

Abstract: Macrophages are specialized phagocytes that play central roles in immunity and tissue repair. Their diverse functionalities have led to an evolution of new allogenic and autologous macrophage products. However, realizing the full therapeutic potential of these cell‐based therapies requires development of imaging technologies that can track immune cell migration within tissues in real‐time. Such innovations will not only inform treatment regimens and empower interpretation of therapeutic outcomes but also enabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…31 In addition, the team of Medina et al reported a liquid PFC nanoemulsion via spontaneous assembly, undergoing a US directed liquid-to-gas phase transition to convert into echogenic microbubbles in situ and enabling on-demand, real-time, and continuous acoustic imaging of macrophages within porcine coronary arteries. 32 In conclusion, PFC gasfilled microbubbles show great potential in in vivo vascular imaging.…”
Section: 1mentioning
confidence: 90%
“…31 In addition, the team of Medina et al reported a liquid PFC nanoemulsion via spontaneous assembly, undergoing a US directed liquid-to-gas phase transition to convert into echogenic microbubbles in situ and enabling on-demand, real-time, and continuous acoustic imaging of macrophages within porcine coronary arteries. 32 In conclusion, PFC gasfilled microbubbles show great potential in in vivo vascular imaging.…”
Section: 1mentioning
confidence: 90%
“…Work from our lab has shown that non-canonical amino acids can be directed to assemble at fluorous-water interfaces to develop mechanically responsive thin films and viscoelastic synthetic mucus (Miller & Medina, 2024;Sloand, Culp, et al, 2021;Sloand, Rokni, et al, 2021). Mechanistic insights gained from this work enabled the development of fluorine-rich small molecules and peptides that act as emulsifiers to stabilize perfluorocarbon nanodroplets (Kim et al, 2023;Lawanprasert et al, 2021;Medina et al, 2017;Sloand et al, 2020;Sloand, Culp, et al, 2021;Sloand, Rokni, et al, 2021). By controlling the physicochemical properties of the emulsifier, we have shown that the thermodynamic stability of phase separated emulsions can be rationally tailored to enable thermally and mechanically responsive nanomaterials.…”
Section: Liquid-liquidmentioning
confidence: 99%
“…In our group, we have exploited these unique properties to create ultrasound-sensitive liquid nanoemulsions for diagnostic and drug delivery applications (Medina et al, 2017;Sloand et al, 2020;Sloand, Culp, et al, 2021;Sloand, Rokni, et al, 2021). Through this work, we have demonstrated that controlling the assembly pathway of the peptide emulsifier at the liquid-liquid emulsion interface can yield nanoparticles with tunable acoustic sensitivity, cellular internalization, and in cellulo stability (Figure 8) (Kim et al, 2023). In particular, Pickering emulsions, which are particles stabilized by the accumulation of solid matter at the liquid-liquid interface (Aveyard et al, 2003;Zhao et al, 2020), can be generated by creating peptide-based fibers and sheets at the interphase.…”
Section: Liquid-liquidmentioning
confidence: 99%
See 1 more Smart Citation